Modulation of the intestinal microbiota in childhood and its interference in the immune system (Research, Society and Development, 2022)
To describe the influence of food on the process of intestinal dysbiosis and food allergies. Therefore, through a literature review, it is proposed to investigate children, in the period of early childhood and pregnant women, since the colonization process starts from the intrauterine period, allowing a greater understanding of the phenomena interconnected with the comorbidities addressed through a search in the databases from Scielo, Sicence Direct, NCBI, university databases, PUBMED, books, newspapers and magazines. Among the inclusion criteria, it is mentioned: publication in the last 10 years, national and international literature and that was related to the proposed objective. As an inclusion criterion, abstracts of event proceedings were included, which were incomplete or which were not available free of charge in full. It was found that, in recent decades, there has been an increase in food allergies in children and it has been found that the intestinal microbiota is closely linked to the maturation process of the immune system. The present work shows how eating habits and environmental factors interfere with intestinal colonization and the possible development of allergies.